(untitled) (American Journal of Islam and Society, 2009)
The Maghrib in the New Century: Identity, Religion, and Politics offers a timely addition to the literature on North Africa. Edited by Bruce Maddy- Weitzman and Daniel Zisenwine, this collection explores the socioeconomic and political challenges facing North Africa in the twenty-first century. The editors have divided the book into four sections broadly concerned with history and identity; the status of the ruling regimes in the face of processes such as globalization and Islamism; economic development; and the North African presence in France. Benjamin Stora’s introduction to the collection neatly sums up many of the issues this region faces, including the aftereffects of colonialism, the fallout from the Algerian civil war, identity movements and the questioned legitimacy of ruling regimes, emigration, terrorism, and battles overwomen’s status. In the first section, Mickael Bensadoun analyzes Moroccan national identity under the nascent rule ofMohammedVI. This is followed by Robert Mortimer’s examination of Algerian identity through literature. Maddy- Weitzman’s essay provides an insightful discussion of how Berber/Amazigh activists have sought to construct Amazigh identity in both Algeria and Morocco by reinterpreting history. The collection segues into a longer section focusing on the political challenges facing the region’s dictatorial regimes, particularly inAlgeria and Morocco. In the fallout from the Algerian civil war, analyses of the current situation in Algeria by Gideon Gera, Louisa Aït-Hamadouche, and Yahia Zoubir are particularly welcome. Zisenwine analyzes the first eight years of Mohammed VI’s rule, while Michael Willis gives a thorough overview of that country’s Islamist movements. Finally, in one of the few pieces to concentrate on Tunisia,Michele PennerAngrist offers a number of astute explanations for the strength of the Ben Ali regime ...